Designing a Budgeting System with Planned Confusion - WILLIAMS, John Joseph (Institutional Knowledge at Singapore Management University, 1981)
The article explores the potential virtues of dual budgeting processes coexisting within a single budgeting information system for organizations experiencing changing environments. The treatment of discretionary cost activity in the traditional budgeting process is discussed and a comparison of the effectiveness of the techniques of zero-based budgeting and traditional budgeting is presented. Using both approaches simultaneously is said to hold potential for combining the best of both methods, but the cost-effectiveness of such a dual budgeting process is noted as a limiting factor.